2001
DOI: 10.1021/nl0100116
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle-Based Sensing of “Spectroscopically Silent” Heavy Metal Ions

Abstract: A simple colorimetric technique for the detection of small concentrations of aqueous heavy metal ions, including toxic metals such as lead, cadmium, and mercury, is described. Functionalized gold nanoparticles are aggregated in solution in the presence of divalent metal ions by an ion-templated chelation process; this causes an easily measurable change in the absorption spectrum of the particles. The aggregation also enhances the hyper-Rayleigh scattering (HRS) response from the nanoparticle solutions, providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
646
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 914 publications
(656 citation statements)
references
References 16 publications
6
646
0
4
Order By: Relevance
“…A colometric approach similar to the one already described above for DNA was recently used to probe for heavy metal ions, including toxic metals such as lead, cadmium, and mercury (166). The method is based on 11-mercaptoundecanoic acid functionalized gold particles, which are aggregated in solution in the presence of divalent ions by an ion-templated chelation process.…”
Section: Applications Of Metal Nanoparticles As Sensorsmentioning
confidence: 99%
“…A colometric approach similar to the one already described above for DNA was recently used to probe for heavy metal ions, including toxic metals such as lead, cadmium, and mercury (166). The method is based on 11-mercaptoundecanoic acid functionalized gold particles, which are aggregated in solution in the presence of divalent ions by an ion-templated chelation process.…”
Section: Applications Of Metal Nanoparticles As Sensorsmentioning
confidence: 99%
“…Although they have not presented any data for Hg 2+ ion, they have indicated that similar responses were obtained with Hg 2+ -and Cd 2+ -containing solutions. Due to the lack of selectivity, the gold nanoparticle-based HRS assay reported by Kim et al 17 cannot be applied to detect heavy metal ions from environmental samples. Here we report a highly selective and sensitive HRS assay for mercury (II) recognition at 5 ppb level in aqueous solution using gold nanoparticles modified with mercaptopropionic acid (MPA), homocystine (HCys), and 2,6-pyridinedicarboxylic acid (PDCA).…”
Section: Introductionmentioning
confidence: 99%
“…decanoic acid (11-MUA) [32], 3-mercaptopropionic acid (3-MPA) [33] and dithioerythritol (DTET) [34]. However, masking agents such as 2,6-pyridinedicarboxylic acid (PDCA) [35] and ethylene diamine tetraacetic acid (EDTA) [34] must be added to improve the selectivity in these colorimetric assays.…”
Section: Science China Materialsmentioning
confidence: 99%